2007
DOI: 10.1080/03014220709510063
|View full text |Cite
|
Sign up to set email alerts
|

First report on the stomach contents of long‐finned pilot whales, Globicephala melas, stranded in New Zealand

Abstract: Stomach contents of the long-finned pilot whale, Globicephala melas, are reported for the first time from New Zealand waters. Analyses based on two male and three female whales (2.5-5.3 m in length) that stranded on Farewell Spit, Golden Bay, South Island in December 2005 revealed a diet comprised exclusively of cephalopods (2−33 lower cephalopod beaks per stomach). Two genera of cephalopod from two orders; arrow squid, Nototodarus spp. (Teuthoidea: Ommastrephidae), and common octopus, Pinnoctopus cordiformis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…), and secondarily octopus (Pinnoctopus cordiformis) ( Table 2). These findings are consistent with earlier accounts from this area (Beatson 2007a; Table 2). Based on the known life histories of both Nototodarus spp.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…), and secondarily octopus (Pinnoctopus cordiformis) ( Table 2). These findings are consistent with earlier accounts from this area (Beatson 2007a; Table 2). Based on the known life histories of both Nototodarus spp.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the known life histories of both Nototodarus spp. and Pinnoctopus cordiformis, Beatson et al (2007a) suggested that long-finned pilot whales stranded in the vicinity of Golden Bay had previously been foraging both near the surface of the water column and on the sea bed, most likely at depths shallower than 150 m. The same would appear true for those whales involved in the 2008 stranding and is relatively consistent with, albeit somewhat shallower than, the foraging behaviour of long-finned pilot whales reported elsewhere. For example, Gannon ( 1995) suggested that long-finned pilot whales off the east coast of the United States foraged at 70-165 m in depth, while Desportes & Mouritsen (1993) suggested that around the Faroe Islands this species feeds at depths between 100 and 500 m. Time-depth recorders deployed on longfinned pilot whales in the Ligurian Sea have recorded foraging dives of between 72 and 648 m (Baird et al 2002).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations